Activity and safety of oral etoposide in pretreated patients with metastatic or recurrent thymic epithelial tumors (TET): A single-institution experience. (September 2016) - Bluthgen, M.V.; Boutros, C.; Fayard, F.; Remon, J.; Planchard, D.; Besse, B.
Highlights: There is no standard treatment for pretreated advanced thymic epithelial tumors (TET). Single agent oral etoposide has not been evaluated in metastatic or recurrent TET. This retrospective study showed single agent etoposide activity in pretreated TET. Myelosuppression was common with etoposide but manageable. Abstract: Objectives: Standard regimens in pretreated advanced TETs are lacking. Single agent responses have been reported with pemetrexed, gemcitabine and targeted therapies. Oral etoposide monotherapy has a favorable safety and efficacy profile in other tumor types. We assessed its activity and safety in advanced or recurrent pretreated TETs. Patients and methods: We conducted a retrospective analysis of patients with advance or recurrent TET treated with single agent oral etoposide at Gustave Roussy (GR) between 1992 and 2015. Efficacy analyses was made by treating physician according to RECIST and retrospectively collected from medical records. Kaplan-Meier method was used to estimate progression-free survival (PFS) and overall survival (OS). Results: Twenty patients were included. Median age was 62 years [range 34–88], 60% were male, 25% had thymoma (T) and 75% had thymic carcinoma (TC). Myasthenia gravis was reported in 15% of them. A median of 2 [range 0–7] prior chemotherapy regimens had been administered, with 60% exposed to etoposide (VIP 40%, carboplatin-etoposide 15%, BEP 5%). Median follow-up since etoposide was 7 years [range 0.5–8.9]. Three patients achieved partial response and nine had stable disease, giving an overall response rate of 15% [T: 20%, TC: 13%] and a 60% disease control rate [T: 100%, TC: 46%]. Median PFS was 4 months [95%CI 3–14] and median OS was 41 months [95%CI 6–86]. Median PFS for T and TC were 21 months [95%CI 9–42] and 4 months [95%CI 2–4]; median OS were 99 months [95%CI 43–not reached] and 13 months [95%CI 4–41], respectively. The most common grade 3–4 related events occurred in 9 patients (45%) and were neutropenia followed by anemia and thrombocytopenia. Conclusion: Oral etoposide monotherapy is an active option for pretreated TET patients, with manageable toxicity profile.